Studi Perencanaan Konsolidasi Dam di Sungai Mujur Desa Pasrujambe Kecamatan Pasrujambe Kabupaten Lumajang - Pambudi, Yan Ahmad Christy; Dermawan, Very (Jurnal Mahasiswa Jurusan Teknik Pengairan, 2018)
Gunung Semeru adalah salah satu gunung api paling aktif di Indonesia. Letusan GunungSemeru pada umumnya berlangsung singkat dan relatif kecil, akan tetapi berlangsung 10-20 menitsekali sepanjang tahun. Sungai Mujur merupakan salah satu sungai yang berada di DAS Mujur yangmembawa aliran material hasil letusan Gunung Semeru. DAS Mujur mempunyai luas DAS 44,904km2 dengan panjang sungai utama 16,95 km2. Pada musim hujan dengan intensitas tinggi dan durasiyang lama, terjadi  mass movement yang membawa material seperti batu-batuan, kerikil, dan pasirkarena slope sungai yang cukup curam. Kondisi alur dan dasar sungai yang membawa material hasilletusan harus dilakukan pengaturan, terutama pada bagian tikungan sungai agar proses agradasi dandegradasi di sungai terkendali. Analisa debit banjir rancangan kala ulang 25 tahun menggunakanmetode Hidrograf Satuan Sintetis Nakayasu sebesar 155,367 m3/dt, sedangkan debit desain untukbangunan konsolidasi dam dengan mempertimbangkan konsentrasi aliran sedimen sebesar 204,424m3/dt. Volume sedimen sekali banjir dengan kala ulang 25 tahun sebesar 199.918,30 m. Bangunankonsolidasi dam akan direncanakan dengan jarak ±215 m sebelah hilir tikungan sungai. Detail dimensibangunan konsolidasi dam yaitu tinggi main dam 3 m, lebar pelimpah 100 m, tebal mercu main dam2,5 m, kedalaman pondasi 2 m, tinggi sub dam 0,75 m dan tebal mercu sub dam 2,5 m.Mount Semeru is one of the most active volcanoes in Indonesia. The eruption of MountSemeru generally takes a short time and is relatively in a small scale, but lasts for 10-20 minutes athroughout the year. Mujur River is one of rivers located in the Mujur watershed that brings the flowof materials from the eruption of the Mount Semeru. In addition, the Mujur watershed has a total DASarea of 44,904 km2 with the main river length of 16.95 km2. During the rainy season with highintensity and long duration, a mass movement occurs and carries materials such as rocks, gravel, andsand due to the quite steep river slope. Therefore, the condition of the river channel and riverbedcarrying the eruption materials should be arranged, especially in the bend section of the river so thatthe process of agradation and degradation in the river may be controlled. Also, the flood dischargeanalysis of 25-year return period design using the Nakayasu Synthetic Unit Hydrograph method is155.367 m3/dt, while the design debit for consolidation of dam by considering the effect of sedimentconcentration is amounted to 204,424 m3/dt. The one-time flooded sediment volume with a 25-yearreturn period is 199,918.30 m3. Futhermore, the consolidation dam building will be planned in distanceof±215mdownstreamoftheriverbend.Moreover,thedetaileddimensionoftheconsolidationdambuilding are the height of the main dam is 3 m, the width of the main dam weir is 100 m, thethickness of the main dam is 2,5 m, footing depth is 2 m, the height of the sub dam is 0,75 m and thethickness of the sub dam is 2.5 m.